2017
DOI: 10.1021/acs.biochem.7b00409
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Polyphenol-Specific Innate Epitopes That Originated from a Resveratrol Analogue

Abstract: Polyphenols have received a significant amount of attention in disease prevention because of their unique chemical and biological properties. However, the underlying molecular mechanism for their beneficial effects remains unclear. We have now identified a polyphenol as a source of innate epitopes detected in natural IgM and established a unique gain-of-function mechanism in the formation of innate epitopes by polyphenol via the polymerization of proteins. Upon incubation with bovine serum albumin (BSA) under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Hence, to determine if oxidation products of Bt-APA function as an innate epitope, we fractionated the products obtained by incubating the lysine analog with ESM by HPLC, and the immunoreactivity of each fraction with natural IgM antibodies was evaluated. For this purpose, IgM mAb SBM3, showing specificity to the EGCG-modified proteins ( 17 ), established from specific pathogen-free–maintained BALB/c mice was used. The ELISA analysis of the HPLC fractions indicated that the antibody has an immunoreactivity with multiple fractions containing products I to III ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, to determine if oxidation products of Bt-APA function as an innate epitope, we fractionated the products obtained by incubating the lysine analog with ESM by HPLC, and the immunoreactivity of each fraction with natural IgM antibodies was evaluated. For this purpose, IgM mAb SBM3, showing specificity to the EGCG-modified proteins ( 17 ), established from specific pathogen-free–maintained BALB/c mice was used. The ELISA analysis of the HPLC fractions indicated that the antibody has an immunoreactivity with multiple fractions containing products I to III ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study ( 16 ) showed that innate IgM antibodies recognized EGCG-treated proteins and speculated on the involvement of polyphenol-mediated electrical conversion of proteins in antibody recognition. Then, based on the discovery that protein polymerization is involved in the crossreactivity of polyphenol-derived epitopes with IgM, we provided the basis for the hypothesis that they may be due, at least in part, to polymerized proteins ( 17 ). However, despite these extensive research efforts on the identification of structural elements of modified proteins involved in recognition by natural antibodies, few studies have clearly shown the structure of the epitope.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Free amino content groups in HPI were expected to decrease after covalent bonding with EGCG, because the amino acid residues bind to quinone after EGCG oxidation. The ε-amino group contained in lysine was oxidized to form a carbonyl group, and a condensation reaction occurred with the free amino groups, thus reducing the number of amino groups [ 29 ].…”
Section: Resultsmentioning
confidence: 99%